Performance reputation. The subject at the intersection of meaning and value - Calzeroni, Pablo (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In this paper, the concept of performative reputation is developed to describe how the construction of our subjectivity is organized by the digital platforms we use to communicate and work. If the value of reputation, first and foremost economic, is defined by our performance through surveillance and validation devices, its social meaning depends on the imaginary narratives that those performances are able to evoke, allowing others to recognise us and ourselves to measure the success of our self-brand.